Is Rehabilitation Essential in the Probation Service in West Bengal? - Chakrabarti, Nirmal Kanti (International journal of offender therapy and comparative criminology, 1992)
All the Probation Service Agencies adopt a rehabilitation programme to help the probationers for their ultimate return to normal life. This author from his study of probationers regarding their socioeconomic conditions in West Bengal, India, asks: "Is rehabilitation essential in Probation Service?" The study is based on (1) official data, (2) house-to-house survey, and (3) field observations